RANCANG BANGUN COMPANY PROFILE GABUNGAN PERUSAHAAN KONSTRUKSI NASIONAL INDONESIA (GAPEKSINDO) BERBASIS WEB - Wiwik Widiyatni; Vilianty Rafida; Ita Arfyanti (Jurnal Ilmiah Matrik, 2021)
Research on Web-based Company Profile Design of the Association of Indonesian Construction Companies (GAPEKSINDO) is a research to make it easier for people to obtain complete and up-to-date information because information is considered very important in decision making and in achieving goals. In addition to obtaining complete and up-to-date information, the website can also send and publish information to the wider community online. The system development method used in this research is the System Development Life Cycle (SDLC) method, or better known as the system development life cycle in system engineering and software engineering, is the process of making and changing systems and the models and methodologies used to develop these systems. The research results are expected that this system can publish its activities for more up-to-date information so that the public can find out about the activities that have been carried out, the ease of information about GAPEKSINDO.